Performance and reference data in the jump squat at different relative loads in elite sprinters, rugby players, and soccer players - Loturco, I.; McGuigan, M. R.; Freitas, T. T.; Valenzuela, P. L.; Pereira, L. A.; Pareja-Blanco, F. (Biology of Sport, 2021)
The aims of this study were to compare the outcomes and provide reference data for a set of barbell mechanical parameters collected via a linear velocity transducer in 126 male sprinters (n = 62), rugby players (n = 32), and soccer players (n = 32). Bar-velocity, bar-force, and bar-power outputs were assessed in the jump-squat exercise with jump-squat height determined from bar-peak velocity. The test started at a load of 40% of the athletes` body mass (BM), and a load of 10% of BM was gradually added until a clear decrement in the bar power was observed. Comparisons of bar variables among the three sports were performed using a one-way analysis of variance. Relative measures of bar velocity, force, and power, and jump-squat height were significantly higher in sprinters than in rugby (difference ranging between 5 and 35%) and soccer (difference ranging between 5 and 60%) players across all loads (40-110% of BM). Rugby players exhibited higher absolute bar-power (mean difference = 22%) and bar-force (mean difference = 16%) values than soccer players, but these differences no longer existed when the data were adjusted for BM (mean difference = 2.5%). Sprinters optimized their bar-power production at significantly greater relative loads (%BM) than rugby (mean difference = 22%) and soccer players (mean difference = 25%); nonetheless, all groups generated their maximum bar-power outputs at similar bar velocities. For the first time, we provided reference values for the jump-squat exercise for three different bar-velocity measures (i.e., mean, mean propulsive, and peak velocity) for sprinters, rugby players, and soccer players, over a wide range of relative loads. Practitioners can use these reference values to monitor their athletes and compare them with top-level sprinters and team-sport players.